Think tank networks and the knowledge-interest nexus. The case of climate change - Dieter Plehwe (Climate Change Denial and Public Relations. Strategic Communication and Interest Groups in Climate Inaction, 2019)
In recent times, no subject matter has provoked stronger practical science wars than the question of climate change, its human causes, and its policy implications. This chapter addresses this conflict constellation, as an extreme case, to highlight its particular relevance to policy-related think tanks and think tank networks. These are the core subject of this chapter, along with the rise of transnational expert, consulting, and lobby/advocacy agencies that appear increasingly to rely on a growing number (or "a new breed") of partisan and contract think tanks employed strategically to achieve political ends. Since the political character of knowledge has to be considered a normal rather than an extraordinary feature of policy-related knowledge, the expertise-interest nexus and the expertise-lobbying feature are relevant way beyond the arguably extreme case of climate change. Yet think tank studies so far have not been sufficiently directed to meet the challenges posed by this new type of transnational political technocracy. Think tank network studies are introduced here as a promising way to improve understanding of the knowledge-interest nexus in transnational knowledge regimes.
Additional information: This chapter was first published in Critical Policy Studies (2014, volume 8, issue 1, pp 101–115, doi: 10.1080/19460171.2014.883859). The author thanks the publisher for granting permission of publication.; Older version: doi:10.1080/19460171.2014.883859
Keywords: 300; transnational networks; think tanks; knowledge–interest nexus; climate change